2014
DOI: 10.1093/jac/dku197
|View full text |Cite
|
Sign up to set email alerts
|

Presence of disinfectant resistance genes in Escherichia coli isolated from retail meats in the USA

Abstract: The QAC resistance genes were commonly present among E. coli isolated from retail meats, and the qac and sugE(p) genes were highly associated with multidrug resistance phenotypes. Using QACs in the food industry may not be as effective as expected and could provide selection pressure for strains with acquired resistance to other antimicrobials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 35 publications
6
85
0
7
Order By: Relevance
“…Investigations of bacterial strains recovered from the field have yielded some evidence of associations between biocide use and reduced susceptibilities to antimicrobial agents. Elevated MIC values for QACs were frequently observed among E. coli recovered from meat in the United States, where such agents commonly are used as sanitizers (Zou et al., ). A strong association was found between the frequent disinfection of pens and colonization of nursery piglets with MRSA, with isolates universally encoding genes ( qac, smr ) responsible for reduced susceptibility to QACs (Slifierz, Friendship, & Weese, ).…”
Section: Disinfectionmentioning
confidence: 99%
“…Investigations of bacterial strains recovered from the field have yielded some evidence of associations between biocide use and reduced susceptibilities to antimicrobial agents. Elevated MIC values for QACs were frequently observed among E. coli recovered from meat in the United States, where such agents commonly are used as sanitizers (Zou et al., ). A strong association was found between the frequent disinfection of pens and colonization of nursery piglets with MRSA, with isolates universally encoding genes ( qac, smr ) responsible for reduced susceptibility to QACs (Slifierz, Friendship, & Weese, ).…”
Section: Disinfectionmentioning
confidence: 99%
“…41 DNA template was prepared by suspending an overnight culture in 600 ml of reagent grade water. The suspensions were heated at 100°C for 10 min and centrifuged at 13,000 rpm for 5 min.…”
Section: Detection Of Qac Resistance Genesmentioning
confidence: 99%
“…39 With the exception of the mdfA gene, which belongs to the major facilitator super family, other genes observed are members of the small multidrug resistance (MDR) family. 1,41 Some reports also indicated that the widespread use of QACs in hospitals, healthcare facilities, food industries, and environment may contribute to the emergence of antimicrobial-resistant microbes. 3,19 Previous studies showed that disinfectant resistance genes, qacE, qacEÄ 1, qacF, qacG, and sugE(p), are located in mobile genetic elements and linked (coexist) with different antibiotic resistance genes.…”
Section: Introductionmentioning
confidence: 99%
“…These different potential sources include personnel, equipment and surfaces and provide one possible explanation for the differences in resistance which can be observed when comparing bacteria from animals and bacteria from meat derived from those animals. In particular, indirect selection for bacterial sub-populations, in the immediate environment and on equipment and surfaces of the production line, following exposure to antibacterial substances other than pharmaceuticals, could result in a decrease in susceptibility to antimicrobials (Zou et al, 2014).…”
Section: Rationale For the Analysis Of Consumption And Resistance In mentioning
confidence: 99%